2020
DOI: 10.1186/s13287-019-1534-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mesenchymal stem cell-derived extracellular vesicles in vitro and their role in ageing

Abstract: IntroductionThis study assessed whether mesenchymal stem cell (MSC)-derived extracellular vesicles influenced ageing and pluripotency markers in cell cultures where they are added.MethodsMSC-derived extracellular vesicles from old and young rat bone marrows were isolated by ultracentrifugation and were characterised by western blotting, nanoparticle tracking analysis (NTA) and transmission electron microscopy (TEM). They were added to young and old MSC cultures. Real-time quantitative reverse transcription pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…Recently, it was demonstrated that incubation of old MSCs with exosomes from young MSCs reduced ageing markers and the mTOR pathway proteins, whereas up‐regulated the pluripotency markers in those cells. Further scrutiny showed that exosomal miRNA‐188‐3p was involved in ageing by regulating the mTOR complex 75 . These findings provide the idea that MSCs‐Exo may be used for the progress of novel therapies against ageing‐associated diseases.…”
Section: Distinct Effect Of Mscs‐exo On Ageingmentioning
confidence: 84%
“…Recently, it was demonstrated that incubation of old MSCs with exosomes from young MSCs reduced ageing markers and the mTOR pathway proteins, whereas up‐regulated the pluripotency markers in those cells. Further scrutiny showed that exosomal miRNA‐188‐3p was involved in ageing by regulating the mTOR complex 75 . These findings provide the idea that MSCs‐Exo may be used for the progress of novel therapies against ageing‐associated diseases.…”
Section: Distinct Effect Of Mscs‐exo On Ageingmentioning
confidence: 84%
“…On the other hand, Oct4, the pluripotency markers which associated with the differentiation potential of BMSCs [43], decreased after differentiation. Oct4 was lower for cells cultured on the APB system than on TCF with signi cant difference after day 5 without GF, but lower with signi cant difference from day 3 with GF.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, Oct4, the pluripotency markers which associated with the differentiation potential of BMSCs [40], decreased after differentiation. Oct4 was lower for cells cultured on the APB system than on TCF with signi cant difference after day 5 without GF, but lower with signi cant difference from day 3 with GF.…”
Section: Discussionmentioning
confidence: 96%